Validity of the social communication questionnaire in adults with intellectual disabilities and suspected autism spectrum disorder - Sappok, Tanja; Bölte, Sven (American journal on intellectual and developmental disabilities, 2015)
This study examined the validity of the Social Communication Questionnaire (SCQ) to identify autism spectrum disorder (ASD) in 151 adults with intellectual disabilities (ID) in Germany. Sensitivities and specificities for ASD were 98/47% for the SCQ-current version and 92/22% for the SCQ-lifetime version. Sensitivities and specificities were increased to 89/66% and 78/48% by adjusting the recommended cut-points. The SCQ-current score correlated with the Scale for Pervasive Developmental Disorders in Mentally Retarded Persons and the Autism Diagnostic Observation Schedule, whereas the SCQ-lifetime score correlated with the Autism Diagnostic Interview-Revised. Our findings support the use of the SCQ-current version for ASD screening in adults with ID, although the SCQ-lifetime version should be used with caution in this population.